Alternativas Para El Mejoramiento Del Comportamiento De Los Estudiantes Provenientes De Hogares Disfuncionales Que Estudian En La Unidad Educativa “San Carlos”, De La Parroquia San Carlos. - Pin Zamora, . Dolores (2014)
The Present Investigation Was Established Alternatives For Improving The Performance Of Students And Homes From Dysfunctional Studying In Educational Unit "San Carlos" Carlos San Parish. The Methodology Proposed In The Research Was Oriented In The Application Of The Types Of Research Consisted Of Field, Bibliographic And Descriptive Whereby The Observation Techniques Implemented, The Survey Of 105 Students And 100 Parents, Where He Was Employed Methods As Inductive - Deductive, Analytical Extract That Allowed Research Analyzing Results That There Is A 62% Of Changes In Student Behavior Is Coming From Dysfunctional Homes. The Proposed Application Of Results Is "Training Plan Methodological Strategies To Improve Student Behavior From Dysfunctional Homes In The Educational Unit" San Carlos ", Which Details Strategies To Improve Relationships Between Parents And Students To Avoid Behavioral Changes, The Proposal Is Based On The Value Orientation To Achieve Change The Environment Of The Learner.